Wild Minds Searching: Early Scholars Groping in the Gap - Scott, Joy; Grellier, Jane (University of Kentucky, 2012)
This paper continues from our earlier co-constructed narrative in which we articulated our struggle as beginning researchers to become authentic, ethical auto-ethnographers. Currently we find ourselves groping in the gap between self and other, seeking to understand its nature and our positionality in this space. Through a multivoiced, multimedia approach, we explore the spaces in which we meet, engage with and represent the participants in our ethnographic research. Ours is a tangled, wiry engagement that reveals our vulnerabilities as we pursue open rather than closed relationships, and write narratives that reveal the personal lived experience of ourselves and others. Borrowing Natalie Goldberg’s notion of ‘wild mind’ and fusing it with Michelle Fine’s (1994) concept of “working the hyphen” with eastern and western art, mythologies and traditional philosophies, we grope in the margins and centres, the spaces and the presences, and the possibilities offered by eastern dialectics to help dissolve the western dualism of self and other.